SUBLIME AND MUSIC IN ADORNO S THOUGHT - HARRISON SILVEIRA (PONTIFÍCIA UNIVERSIDADE CATÓLICA DO RIO DE JANEIRO, 2015)
PONTIFÍCIA UNIVERSIDADE CATÓLICA DO RIO DE JANEIRO === COORDENAÇÃO DE APERFEIÇOAMENTO DO PESSOAL DE ENSINO SUPERIOR === PROGRAMA DE SUPORTE À PÓS-GRADUAÇÃO DE INSTS. DE ENSINO === O presente texto propõe verificar o sublime e a música em Adorno. Para tanto, três objetivos centrais serão seguidos. O primeiro visa verificar o surgimento do sublime. De objeto de investigação filosófica do tratado Do Sublime atribuído à Longinus e a posterior tradução, por Boileau, avançaremos para a sua recepção e repercussão na Inglaterra oitocentista, especificamente, Burke. Em seguida, analisaremos o sublime em Kant, visando dialogar com as considerações adornianas a cerca do sublime, configurado pelo filósofo como enigma, e as obras de vanguardas artísticas, a Nova Música. O segundo objetivo debruça-se sobre a Nova Música, verificando sua contribuição para o entendimento do sublime em Adorno. Para tanto, analisaremos as possíveis ligações e desdobramentos presentes nesta nova proposta radical musical, denominada por Adorno, de esfera despadronizada, quando, comparadas à esfera de obras musicais, ditas, padronizadas. Formularemos a hipótese de que a Nova Música esteja imbricada, tanto com o sublime em Burke, notadamente, via expressionismo musical, bem como, com o sublime matemático kantiano, dada à incomensurabilidade de suas possibilidades composicionais advindas do dodecafonismo schonberguiano, para finalmente receber, em Adorno, o tratamento de enigma. O terceiro e último objetivo foca no fetichismo musical e o seu desdobramento em regressão auditiva, decorrência principal, nas artes musicais, da Indústria Cultural. Mediante tal análise, aventaremos a hipótese, de que a regressão auditiva, paradoxalmente aos sombrios prognósticos adornianos, descortinou também, os novos rumos para a música ocidental. Através da liberação das dissonâncias e do uso da série, advindas da mesma Segunda Escola de Viena, surgiram os movimentos de música concreta, eletrônica e eletroacústica, permitindo-se um novo tratamento musical para o ruído, transformando-o assim, no mais novo elemento composicional. As conclusões centralizam-se na questão principal da categoria estética artística musical, o sublime. Por meio de sua análise, interpretação e entendimento, permite-se uma aproximação ao tratamento dado por Adorno a certas obras musicais, sinalizadas pelo filósofo, como pertencentes ao âmbito do sublime musical. Esperamos contribuir, com esta pesquisa, para uma maior aproximação com o sublime e a crítica musical em Adorno. === This dissertation focuses on Adorno s treatment of the music phenomenon under aesthetic s category of the sublime. To do so, we will follow three main goals. The first one deals with the debate of the sublime in Philosophy. Its beginning as an object of philosophical enquiry since Do Sublime Treaty, attributed to Longinus, appeared for the first time in history. It s enduring echos in France through its French translation by Boileau, as well its reception and repercussions in the eighteenthcentury England with Burke s Philosophical Enquiry into the Origin of our Ideas of the Sublime and the Beuatiful. Kant s sublime will be analyzed shortly afterwards, in order to deal with Adorno s considerations on the sublime and the avantgard movements. Our attention will be focused on the enigmatic element which was analyzed by Adorno in some artworks, especially those of the New Music stream. Our second goal is about the discussion of the Adornian concepts of New Music.Our aim here is to decide whether these concepts as presented by Adorno, can still be of any use to understand as well as to call music sublime. At the same time it will be analyzed the strong bounds and developments that can t be avoid to be grasped between this new kind of radical musical proposal so called by him as, the sphere of non standardized music, thus drawing a parallel with the standardized music sphere. This will lead us to hypothesize that New Music, as observed by Adorno, is deeply bound up with the Burke s ideas about the sublime, notably seen by means of the music compositions on the expressionism period, as well to Kant s mathematically sublime through the immeasurable possibilities of music compositions brought by the dodecaphonic and serial techniques. As a result, it will be seen by Adorno as a great enigma, a riddle, a puzzle, due to its mystery nature which never allows to be entirely signified. On our final goal we intend to examine the regression of listening as the main after effect of the Culture Industry on music by means of the Fetish-Character, which is directly responsible for a turnaround of artworks into commodities whose only fate will be to serve as goods, thus being consumed by the majority. Paradoxically Adorno s voice of doom about the regression of listening in our modern society can be hypothesized today as a new path for western music. The full usage of the noise which was the one of the mainly results of the dissonance s freedom promoted by the same Second Viennese School which Adorno was a zealous believer, a new tool for the contemporary music composition was devised. By turning the noises into a new compositional tool through the serialism technique, the post modern music has arrived. Our conclusions attempts to centralize around the main question of the aesthetic s category of the sublime in music. By its analysis, as well as its interpretation and its knowledgement, it can lead us the way to approach and elucidate Adorno s treatment of certain music artworks as belonging to the sublime realm. We truly hope to have provided with this research a reliable contribution to music critique not only those belonging to the realm of New Music but, to all the new music artworks, that follow its streams throughtout the XX century and beyond.